Structural Design of A Linear-Motion Type Semi-Active Damper by Finite Element Method - ADACHI, Takahito; TAKAHARA, Kenji (International Journal of Natural Sciences Research, 2017)
The purpose of this study is to design a structure of a linear-motion type semi-active damper which can reduce the vibration caused by an earthquake. This paper proposes the more effective structure of the linear motion semi-active damper by magnetic-structure interaction analysis of finite element method using ANSYS. The semi-active damper has a simple structure that a linear mover, a magnet bar, reciprocates in coils of a stator. The size of the coils and the size of the magnetic material cover which can produce the maximum damping force are simulated under the condition that the size of the mover is fixed. The electromotive force is calculated based on the change of the produced magnetic field according to the change of the given velocity of the mover in a short time. The damping force is calculated according to the electric current which the electromotive force supplies to the connected resistance. By the simulations, more than 120 [N s/m] of the maximum damping coefficient is acquired in the case that the coil is wound up from 28.0[mm] of the inner diameter to 60.0 [mm] of the outer diameter.